Microbiome, immune system and cancer: three sides of the one medal - V. A. Belyavskaya; N. V. Cherdyntseva; J. G. Kzhyshkovska; N. V. Litvyakov (Сибирский онкологический журнал)
Purpose of the study to analyze current ideas about the relationship between the microbiota (microbiome) and the human body in the aspect of cancer pathogenesis, ambivalent character of these interactions, and the role of the immune system and immunoinfammatory status that promotes carcinogenesis or prevents neoplastic processes.Material and Methods. Literature search was carried out using Medline, Cochrane Library, Elibrary and PubMed systems, including publications over the last 7 years.Results. The microbiota includes all communities of commensal, symbiotic, and pathogenic microorganisms: bacteria, fungi, archaea, and viruses that colonize the gastrointestinal tract and other organs and tissues. The microbiome is an important factor in cancer pathogenesis due to its involvement in the basic physiological functions of the host, such as digestion, development of the immune system, and modulation of endocrine functions. In the review, the influence of microbiota of different locations (gastrointestinal tract, breast, intravaginal tract) on the development and progression of breast, colorectal and cervical cancers was discussed. The role of the microbiome in cancer pathogenesis is realized by the participation in neoplastic transformation of the epithelium, regulation of tumor progression under conditions of manifested malignant process, and modifcation of the therapeutic effect of standard drugs, including the development of original probiotic-based anticancer agents. The study of the mechanisms of action of the microbiome in the host organism opens up prospects for the development of new approaches to cancer therapy. Particular attention was paid to the mechanisms of the immunomodulatory effect of the microbiota in terms of reducing the risk of malignancy, regulating tumor progression and participating in antitumor therapy. The clinical significance of determining pathogenetically significant microbial markers associated with the aggressive form of cancer, response to treatment and toxicity of therapy was discussed. Particular attention should be paid to the potential mechanisms of interaction between cancer – microbiome – probiotics, since the latter can provide modification of malignancy processes, exert an antitumor effect, and modulate the effectiveness of drug therapy. The feasibility of editing the microbiota by probiotics was considered, and antitumor properties (effects) of bacteria and strategies for modifying the microbiome for the prevention and treatment of cancer were discussed.